"Together we are stronger!" - Vietnamese and Brazilian teachers' stories of difficulties and learning opportunities in online teaching during covid-19: a qualitative study - Tu Anh Hà; Giovanna Caetano-Silva (Universidade Católica Portuguesa, 2021)
The present study aims to investigate challenges and learning opportunities that teachers experienced when shifting from face-to-face to online class[1]rooms during the Covid-19 pandemic. The research is grounded on a qualitative design, and data were collected through a survey from 107 Brazilian and Vietnamese educators. Qualitative content analysis is applied to analyze participants' replies. As a result, the study identifies the following key challenges: (i) mental and emotional issues, (i) interaction inside and outside the classroom, (iii) lack of preparation, (iv) lack of physical access to technology, which is linked to (vi) social inequality in education, and (vii) adaptation of teaching methods. In addition, results of Fisher's exact test show that teachers are significantly different in reporting their challenges, regarding their sectors and countries. In terms of learning opportunities, the study highlights: (i) increasing students' autonomy, (ii) teachers' compassion with students' diffi[1]culties, (iii) possibility of bonding with students, (iv) optimistic attitudes, (v) overcoming difficulties by learning with trials and mistakes, and (vii) professional development and learning. Finally, it showcases that DE can also be a terrain of learning opportunities in which compassion and professional development opportunities take place through, for instance, finding ways for bonding and teaching despite adversity.